Plasma concentrations of high-dose olanzapine in a double-blind crossover study - Kelly, Deanna L.; Richardson, Charles M.; Yu, Yang; Conley, Robert R. (Human psychopharmacology, 2006)
Olanzapine is structurally similar to clozapine but has not been shown at routine doses to share the superiority of clozapine to traditional antipsychotics in treatment‐resistant patients. Olanzapine, however, has been increasingly used in higher doses as clinicians attempt to find a more tolerable therapy for those refractory to conventional agents. This study examined the relationship of high‐dose olanzapine plasma concentrations to symptoms, adverse effects, smoking, and gender. Thirteen patients participated in a double blind 16‐week crossover study (8 weeks each arm) of olanzapine (50 mg/day) compared to clozapine (450 mg/day). Women had significantly higher plasma olanzapine levels than men at each time point in each arm (weeks 4, 6, and 8). At 8 weeks women had a steady‐state olanzapine level of 278 ± 62 ng/ml while men had a steady‐state level of 127 ± 47 ng/ml (p = 0.005). At week 4, olanzapine levels tended to be higher in those who had been on clozapine previously (205 ng/ml) compared to those who received olanzapine in the first arm (105 ng/ml). Cigarette intake was negatively correlated to olanzapine plasma concentrations (week 8: r = −0.86, p < 0.05). Plasma levels were significantly higher in those experiencing constipation (176 vs. 82 ng/ml; p = 0.022). Plasma levels of olanzapine were not associated with symptom response and anticholinergic effects were seen at greater frequency with higher olanzapine concentrations. In conclusion, this study reports plasma olanzapine levels at high fixed doses of olanzapine (50 mg/day) in relation to side effects, symptoms, smoking, and gender. Copyright © 2006 John Wiley & Sons, Ltd.